P226 Impaired respiratory health status in the UK HIV infected population despite the use of antiretroviral therapy. (12th November 2015) - Brown, JP; McGowan, J; Chouial, H; Capocci, S; Smith, C; Ivens, D; Lampe, F; Johnson, M; Sathia, L; Rodger, A; Lipman, M
Abstract : Background: The widespread use of antiretroviral therapy (ART) has led to a reduction in HIV related opportunistic infections. An increase in chronic non-HIV related co-morbidities has been observed in stable HIV positive individuals receiving ART. The extent to which HIV infection remains an independent risk factor for respiratory disease despite the use of antiretroviral therapy is uncertain and few studies have systematically evaluated respiratory disease in HIV-infected populations with access to antiretroviral therapy. Aims: We sought to evaluate the frequency of (a) smoking and (b) respiratory symptoms and (c) spirometric impairment in the ambulatory UK adult HIV infected population, compared to HIV uninfected controls. Methods: HIV-positive participants were recruited from a large HIV care service, HIV uninfected participants were recruited from Sexual Health services (where recruitment was stratified by age to approximate that of the HIV positive subjects). Participants completed a questionnaire which included questions on smoking history and respiratory health status using the St George's Respiratory Questionnaire (SGRQ), and undertook spirometry without bronchodilation. Results: 249 participants were recruited between April and July 2015 (Table 1 ). 28% of HIV positive and 33% of HIV negative participants were current smokers (p = 0.22). 9% of HIV positive and 7% of HIV negative participants had an FEV1 /FVC of <0.7 (p = 0.38). 92% of HIV positive participants were using antiretroviral therapy, 86% had an undetectable plasma HIV viral load and mean CD4 count was 684 cells/µL. Significantly higher SGRQ scores were observed in HIV positive participants than HIV-negative participants with a median total SGRQ score of 12 for those with HIV infection and 8 for the HIV negative participants (p = 0.03). In a linear regression (log scale) model, HIV infection was associated with a 62% increase (95% CI 1.19–2.21, p < 0.01) in SGRQ in unadjusted analysis and 48% increase (1.08–2.02, p = 0.01) in a multivariable analysis adjusting for age, gender and smoking status. Conclusions: Despite widespread use of ART, HIV infection is independently associated with impaired respiratory health status. This does not appear to result from current smoking or obstructive lung disease.